MAIN HERO IMAGE IN THE INTERPRETATION OF THE STORY (Scientific journal of the Fergana State University, 2023)
The article describes the role and importance of Shukur Kholmirzaev's works in the development of modern Uzbek storytelling. Through his portrayal of the main character in the story "Birds Returned from the Village", the tragedy of a person who was a victim of the deception of the Shura ideology and served the calls of his time was convincingly explained. The features of the writer's skill in the interpretation of characters are shown.